PERKAINAN SESUKU DI DESA TANJUNG KECAMATAN KOTO KAMPAR KABUPATEN KAMPAR - Saputri, Melly Dwi; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was undertaken on the basis of the marriage did what happened in the village of tanjung sub-district the Koto Kampar upstream district Kampar . Although marriage kinsmen is opposed to local customs , but it still often occurs. Although marriage kinsmen is opposed to local customs, but it still often occurs. The role of Ninik Mamak was needed to overcome marriage did this. If marriage was indeed contention did customs in country Tanjung , then should it is never going to happen. Then should it is never going to happen. Nevertheless , concomitant development era, as if there is no parapet someone to do the he wants this also could not be solved by Ninik Mamak country Tanjung. Development era is just one of the cause of the occurrence of marriage did. For that , in this research will give the cause of the writer and a result of the marriage the kinsmen . Research is done using that method is purposive sampling, type selection of the subject with no reshuffling of the subject with the consideration and certain criteria. To strengthen the research data obtained, the author also has an informant who considered of controversy with the problems in accordance with research who writers do. A subject in this research is a number of customary or Ninik Mamak stakeholders having social status respected as a person . Ninik Mamak is the important role in the customs and of course already understand about problems marriage did. Besides Ninik Mamak, a member of the local community also included as an informant in this research. Informants who truly important in this research is marriage did agents it self. Customary stakeholders used informants as many as five people , a member of the local community as many as six people and investors marriage did as many as five couples .The results obtained from this research is disapproval from the Ninik Mamak which marriage did indeed this is a subject which have been banned happened since the beginning the customs in country Tanjung . However, for couples and marriages one tribe has already made its desire to maintain that custom is one in the village of Tanjung, they must accept sanctions applied in the village of Tanjung.Keywords: marriage, tribe, causes and Ninik Mamak